Obtenção e caracterização de laminados de compósitos poliméricos híbridos de fibras de juta a partir de laminados de fibras de vidro utilizados na fabricação de pás eólicas - Alves, Jose Leandro Correia (2017)
At last years due to increasing use of composite materials of synthetic fibers with thermosetting matrix, several alterative have been sought trying to minimize the impacts generated by both the dispose of this material at the end of their useful life and by its heavy dependency of non-renewable resources as petroleum based products for the production of raw materials. As alternative to introduce composites materials that have least environmentally impact natural fibers have drawn attention of researchers. In this work the aim is to manufacture by vacuum infusion process, composite laminates hybrid adding woven jute fiber in structural weaving fiberglass with epoxy resin matrix. The quality of laminate was analyzed by fiber weight fraction determining and thermal analysis by DSC (Differential Scanning Calorimetry) and DMTA (Dynamic Mechanical Thermal Analysis). It was possible to manufacture hybrids laminates by vacuum infusion with fiber fraction in about 60%. Hybrids laminates presented had a reduction of density of 20% with relation to the glass reinforced plastic. Regarding to mechanical properties, the laminates were characterized by tensile, compression and ILSS testing. With respect to hybrid laminates, the better results of tensile properties such as strength and young's modulus was achieved by the laminates with fiber oriented in 0/90° (H0/90) with maximum strength value near to 200 MPa, while for orientation ±45° (H45 e H45/0/90) the strength results were 68 MPa and 84 MPa, respectively. In this case can be highlighted the hybrid laminate H45, whose tensile strength (83,9 MPa) has not present significant changes with the introduction of jute fiber (with increase of 60% its thickness) compared with glass reinforced plastic (84,5 MPa) for the same fiber orientation. For compressive strength the best result was presented by the laminates H0/90 (fibers in 0/90°) as well, with values close to 150 MPa while the laminates to ±45° (H45 e H45/0/90) presented values of 90 MPa. Regarding to ILSS the variation of strength was smaller, 25 MPa to direction 0/90° and 23 MPa and 21 MPa to H45 and H45//0/90 laminates, respectively. Therefore, mechanical properties were significantly influenced by plies orientation in the laminates and by the hybridization with jute fibers.